2006
DOI: 10.1002/dvdy.20697
|View full text |Cite
|
Sign up to set email alerts
|

The differentiation and morphogenesis of craniofacial muscles

Abstract: Unraveling the complex tissue interactions necessary to generate the structural and functional diversity present among craniofacial muscles is challenging. These muscles initiate their development within a mesenchymal population bounded by the brain, pharyngeal endoderm, surface ectoderm, and neural crest cells. This set of spatial relations, and in particular the segmental properties of these adjacent tissues, are unique to the head. Additionally, the lack of early epithelialization in head mesoderm necessita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
369
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 355 publications
(384 citation statements)
references
References 255 publications
(229 reference statements)
11
369
1
3
Order By: Relevance
“…The extraocular eye muscle, the lateral rectus, which arises adjacent to the hindbrain and migrates to its final destination was also found to express Tbx1 (position indicated by white arrow in Fig. 1A, also see Noden and Francis-West, 2006). The expression of Tbx1 in myogenic cells was readily apparent by comparison with the expression of the myogenic factors capsulin, MyoR, and MyoD on adjacent sections at stages 20 and 24 (Fig.…”
Section: Expression Analysis Of Tbx1 During Craniofacial and Limb Devmentioning
confidence: 83%
See 3 more Smart Citations
“…The extraocular eye muscle, the lateral rectus, which arises adjacent to the hindbrain and migrates to its final destination was also found to express Tbx1 (position indicated by white arrow in Fig. 1A, also see Noden and Francis-West, 2006). The expression of Tbx1 in myogenic cells was readily apparent by comparison with the expression of the myogenic factors capsulin, MyoR, and MyoD on adjacent sections at stages 20 and 24 (Fig.…”
Section: Expression Analysis Of Tbx1 During Craniofacial and Limb Devmentioning
confidence: 83%
“…This analysis revealed that Tbx1 transcripts are clearly apparent in the mesoderm adjacent to the caudal hindbrain from stage 7, encompassing the region that will give rise to the first and second arch muscles and the lateral rectus muscle (Fig. 3A, black arrow and data not shown; Evans and Noden, 2006; reviewed by Noden and Francis-West, 2006). In contrast, capsulin expression was undetectable in the cranial mesoderm ( Fig.…”
Section: Expression Analysis Of Tbx1 During Craniofacial and Limb Devmentioning
confidence: 87%
See 2 more Smart Citations
“…Typically, myogenic and connective tissue progenitors are induced and begin their differentiations independently (reviews, e.g., limbs: Duprez, 2002;Anakawe et al, 2003;Venters et al, 2004;head: FrancisWest et al, 2003;Noden and Trainor, 2005;Noden and Francis-West, 2006). However, the subsequent morphogenesis of muscles necessitates especially tight integration with their surrounding connective tissues.…”
Section: Introductionmentioning
confidence: 99%